Bilateral Chronic Anterior Cruciate Ligament Tear or Congenital Absence of Anterior Cruciate Ligament? – A Case Report - Alok Sahu; Hemant Sharma; Mohit Asthana; Asgar Ali; Chaitanya Sharma; Nikita Jajodia (Journal of Orthopaedic Case Reports)
Introduction: Congenital absence of the anterior cruciate ligament (ACL), first reported by Giorgi in 1956 is an extremely rare condition. The prevalence of this condition is reported to be around 0.017/1,000 live births. This congenital anomaly can present in isolation or be associated with other skeletal malformations, including fibular hemimelia, congenital femoral deficiencies, and hip dysplasia. Congenital ACL deficiency may often go undiagnosed in early life. Others will eventually experience symptoms due to the long-term effects of knee instability that can lead to chronic knee pain, particularly in the medial knee and patellofemoral compartments, and may predispose individuals to early-onset osteoarthritis. As the condition is extremely rare and can occur with or without associated deformities, there is no single treatment of choice for the condition. Case Report: We herein report a case of bilateral isolated congenital absence of ACL in a 24-year-old young woman who presented to us with the chief complaints of pain in the right knee for the past 2 years and the left knee for the past 10 months. Conclusion: Although good outcomes with conservative management in individuals without symptomatic instability have been reported, surgeons advocate ACL reconstruction in cases presenting with symptomatic instability.